Enhanced anti-tumor therapy for hepatocellular carcinoma via sorafenib and KIAA1199-siRNA co-delivery liposomes - Yao Yao; Qian Zhao; Feng Xu; Tingting Yao (Elsevier, 2024)
Hepatocellular carcinoma (HCC) is one of the most lethal malignancies worldwide. Sorafenib (Sf) is currently the first-line treatment for HCC. However, due to the side effects and unsatisfied efficiency of Sf, it is urgent to combine different therapeutic agents to inhibit HCC progression and increase the therapeutic efficacy. Here, our study constructed a Sf and KIAA1199-siRNA co-loaded liposome Sf-Lp-KIAA, which was prepared by electrostatic interaction of KIAA1199-siRNA and Sf loaded liposome (Sf-Lp). The particle size, zeta potential, the in vitro cumulative release was investigated. The physical and chemical properties were characterized, and the inhibition of HepG2 growth and metastasis in vitro was investigated. The cellular uptake of the co-loaded liposome was significantly higher than that of free siRNA, and the drug/siRNA could be co-delivered to the target cells. Sf-Lp-KIAA could significantly inhibit the growth, migration, invasion and down-regulate KIAA1199 expression of HepG2 cells in vitro than that of single Sf treated group. In addition, the co-delivery liposome accumulated in the HepG2 subcutaneous tumor model and suppress tumor growth after systemic administration without induce obvious toxicity. The present study implied that the co-delivery of Sf and KIAA1199-siRNA through the co-loaded liposomes exerted synergistic antitumor effects on HCC, which would lay a foundation for HCC therapy in the future.